2006
DOI: 10.1262/jrd.18033
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bovine Serum Albumin and Trehalose in Semen Diluents for Improvement of Frozen-Thawed Ram Spermatozoa

Abstract: Abstract. In this study, two following experiments were performed to improve post-thaw motility and viability of frozen-thawed ram spermatozoa. We examined i) the effects of different concentrations of bovine serum albumin (0, 0.3, 1, 5, 10 and 15% BSA) in semen diluents lacking egg yolk and ii) the effects of four semen diluents, fructose (F: control) and trehalose (T) in semen diluents containing egg yolk, 15% BSA in semen diluents without egg yolk (BSA), and modified phosphate buffered saline (m-PBS). Froze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
70
2
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 106 publications
(88 citation statements)
references
References 31 publications
11
70
2
2
Order By: Relevance
“…Bovine serum albumin (BSA) is one of proteins available for replacement of egg yolk [11,12]. Matsuoka et al [13] reported that the rates of postthaw sperm progressive motility were significantly higher in 10% and 15% BSA than in control extender (Tris-fructose-egg yolk) and concluded that 10 or 15% BSA could be substituted in place of egg yolk in a semi-defined semen extender. The present field trial confirmed these laboratory results [13].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Bovine serum albumin (BSA) is one of proteins available for replacement of egg yolk [11,12]. Matsuoka et al [13] reported that the rates of postthaw sperm progressive motility were significantly higher in 10% and 15% BSA than in control extender (Tris-fructose-egg yolk) and concluded that 10 or 15% BSA could be substituted in place of egg yolk in a semi-defined semen extender. The present field trial confirmed these laboratory results [13].…”
Section: Discussionmentioning
confidence: 99%
“…Semen was collected from a Suffolk ram (3 years old) using an artificial vagina and was diluted (semen : extender=1:4) in a water bath (30 C) with one of the two Tris-based extenders containing 297.58 mM Tris, 96.32 mM citric acid, 82.66 mM fructose, 5% (v/v) glycerol, and either 15% (v/v) egg yolk [14] or 10% (w/v) BSA [13]. The diluted semen was gradually cooled to 4 C for 2-3 h. The diluted semen was frozen in 0.25 ml straws according to the methods described previously [13].…”
Section: Artificial Insemination (Ai)mentioning
confidence: 99%
See 2 more Smart Citations
“…Semen cryopreservation is a well-developed technique commonly used worldwide; it extends the life of spermatozoa by decreasing sperm metabolism and toxin production, but induces partially irreversible injury to sperm membranes, which may reduce sperm motility, viability and the fertilization rate after artificial insemination [1][2][3][4][5]. Sperm damage during preservation in liquid nitrogen at -196°C has been attributed by many authors to cold shock, ice crystal formation, oxidative stress, osmotic changes, cryoprotectant toxicity and reorganizations of lipid-protein and phospholipid layers within the cell membranes [6][7][8].…”
Section: Introductionmentioning
confidence: 99%